Analisis Efektivitas Pemungutan Pajak Daerah di Indonesia - Mochammad Miftachul Huda; Amnina Aulia Putri; Muhammad Fatkhur Rohman Nuri; Novi Khoiriawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Regional taxes are one of the source of Local Own-Source Revenue (PAD). However, the effectiveness of regional tax collection in Indonesia faces challenges, such as low taxpayer compliance, limited technological infrastructure, and lack of transparency. This study aims to analyze factors influencing the effectiveness of regional tax collection, employing a literature review method. The results indicate that adopting digital technologies, such as e-Tax systems, enhancing transparency, and improving taxpayer literacy are critical elements in boosting tax revenue. Synergy between technological innovation, taxpayer education, and government accountability is essential for optimizing regional tax collection sustainably.